Comparative analysis of general dental practitioners' fees and scheduled fees for root canal treatment and coronal restorations in the adult population of Sweden: a 5‐year follow‐up of data from the Swedish Dental Register. (20th August 2017) - Wigsten, E.; Kvist, T.; Dawson, V. S.; Isberg, P.‐E.; ,; Fransson, H.
Abstract: Aim: To investigate the fees charged by Swedish dentists for root fillings, coronal restorations and further dental interventions during a follow‐up period of 5–6 years. Methodology: A total of 248 299 root fillings were linked with the tooth, the patient and the provider and entered into the Swedish Social Insurance Agency register in 2009. The data register also recorded the subsidy‐based (scheduled) fee and the fee actually charged for the root fillings. Fees charged for direct or indirect coronal restorations and additional interventions during the follow‐up period were also recorded. One‐wayanova and t ‐test were used for statistical analysis. Results: The mean overall fee charged for a root filling was approximately 332 Euro and differed only marginally (13 Euro) from the scheduled fee. The total mean fee for preservation of a root filled tooth was 717 Euro, which included the root canal treatment, the coronal restoration and any additional interventions during the follow‐up period. The fees for indirectly restored root filled teeth were significantly higher (1105 Euro) than for directly restored teeth (610 Euro), despite further additional treatment ( P < 0.001). The mean fee for teeth which were subsequently extracted was higher (769 Euro) than for the retained teeth (711 Euro) ( P < 0.001). Conclusions: Fees charged by Swedish dentists for root canal treatment were in accordance with the scheduled fees. The overall mean fee was significantly higher for root filled teeth with indirect restorations than for teeth with direct coronal restorations. However, prospective clinical cost‐effectiveness studies are needed to analyse the total costs.